1999
DOI: 10.1073/pnas.96.26.15050
|View full text |Cite
|
Sign up to set email alerts
|

Abundant empty class II MHC molecules on the surface of immature dendritic cells

Abstract: A monoclonal antibody specific for the empty conformation of class II MHC molecules revealed the presence of abundant empty molecules on the surface of spleen-and bone marrow-derived dendritic cells (DC) among various types of antigen-presenting cells. The empty class II MHC molecules are developmentally regulated and expressed predominantly on immature DC. They can capture peptide antigens directly from the extracellular medium and present bound peptides to antigen-specific T lymphocytes. The ability of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 67 publications
3
119
0
1
Order By: Relevance
“…As previously shown (33) and confirmed in this study, class II constitutively expressed by Ii chain mutants has superior peptide-loading capabilities, but it remains unclear whether these molecules are truly empty or occupied by easily displaced ligand(s) that permits properly folded class II to escape endoplasmic reticulum quality control. Recent evidence suggests empty class II molecules are selectively produced by immature dendritic cells (51), possibly due to down-regulated Ii chain expression (52,53). Interestingly, allele-specific Ii chain requirements also appear to regulate dendritic cell functional activities (54).…”
Section: Discussionmentioning
confidence: 99%
“…As previously shown (33) and confirmed in this study, class II constitutively expressed by Ii chain mutants has superior peptide-loading capabilities, but it remains unclear whether these molecules are truly empty or occupied by easily displaced ligand(s) that permits properly folded class II to escape endoplasmic reticulum quality control. Recent evidence suggests empty class II molecules are selectively produced by immature dendritic cells (51), possibly due to down-regulated Ii chain expression (52,53). Interestingly, allele-specific Ii chain requirements also appear to regulate dendritic cell functional activities (54).…”
Section: Discussionmentioning
confidence: 99%
“…A weak induction of AHR measurable only by electrical field stimulation of tracheal smooth muscle preparations, but not by whole body plethysmography was observed (14,40). To amplify the T cell response to peptides, DC have been used in this study because they have been shown to be potent in priming T cells to peptides (5,10,41) in part due to the presence of large number of empty MHC class II molecules on their surfaces ready for peptide loading (42). In addition, peptides have been delivered i.t.…”
Section: Discussionmentioning
confidence: 99%
“…1C), although expressing substantially higher amounts of HLA-DR than iDCs at the cell surface (see below). The rather small difference in peptide loading by iDCs and B cells may be explained by the fact that iDCs, but less so B cells, express empty and thus peptide-receptive MHC class II dimers (21). B cells also formed 1.8-fold more pMHC complexes than iDCs when we pulsed a different peptide (HLA-A2 103-117 ) onto HLA-DR1-positive APCs and detected HLA-DR1-HLA-A2 103-117 complexes by a specific mAb (17) and cytofluorometry (data not shown).…”
Section: Pmhc Complexes On Dcs Are Uniquely Efficient In Down-modulatmentioning
confidence: 99%